High noon on Proxima B - Boop, David; Davis, Milton; Hutcheson, Thea; Ward, Dayton, 1967-; Matthews, Susan R.; Winnig, Cliff; Wacks, Peter J., 1976-; Cooper, Brenda, 1960-; Scholes, Ken; Schwaeble, Hank; Williams, Walter Jon (Baen, 2023)
"Adventure! Danger! Revenge! And a mail-order robot gunslinger in a wedding dress? Only in the wildest parts of space could this happen. It's time again to get in your ramshackle rocket ship and journey to the universe's western territories with this follow-up to Gunfight on Europa Station. Meet the employees of a space bordello as they're drawn together to pull a con on a con. Or the crew filming a Western on a colony ship only to fight gravity and each other. Or a soldier on a backwater planet hiding from her past when it-and the military-finally tracks her down. Each voyage invokes the type of Western yarns you've loved before, but with a science fiction upgrade you'll get to enjoy anew. Taking you on this ride is another set of astounding space opera authors such as Walter Jon Williams (Hardwired), Susan R. Matthews (Under Jurisdiction), Dayton Ward and Kevin Dilmore (Star Trek), Brenda Cooper (Project Earth), Milton Davis (Changa's Safari), John E. Stith (Naught for Hire), and Peter J. Wacks (Caller of Lightning). Ten tales of the West... not as it was, but as it might be!"--